Der Hase mit den Bernsteinaugen das verborgene Erbe der Familie Ephrussi - De Waal, Edmund 1964- (Deutscher Taschenbuch Verlag, 2014)
Traces the parallel stories of nineteenth-century art patron Charles Ephrussi and his unique collection of 360 miniature netsuke Japanese ivory carvings, documenting Ephrussi's relationship with Marcel Proust and the impact of the Holocaust on his cosmopolitan family
Keywords: Ephrussi -- Familie -- ca. 18. Jh.-; Geschichte; Kunst; Netsuke; Privatsammlung; Europa; Japan; Ephrussi family; Jewish bankers / Europe / Biography; Jewish businesspeople / Europe / Biography; Art / Collectors and collecting / Europe / Biography; Netsukes / Private collections / England / London; De Waal, Edmund / Travel / Europe; Biografie; Fiktionale Darstellung